Comparison between Islamic insurance and conventional insurance on construction project / Khairul Ammar Muhammad Ali - Muhammad Ali, Khairul Ammar (2006)
This research is focusing to the application of insurance on construction project. Two different concept of insurance considered on this research are Islamic Insurance and Conventional Insurance. The objective of this research is to find the commonly used of insurance on the construction project and analyzed the advantages and disadvantages of Conventional Insurance and Islamic Insurances on construction project. The scope location is for the contractor that registered at Penang and Klang Valley only. Sometimes, there were a contractor that did not know the advantage and disadvantage of the insurance they used. For them, there was nothing different for any insurance product. Actually, these attitudes give various impacts to their protection of right. The insurance problem is being compounded because many people working in the construction industry have never experienced an unfavorable insurance cycle. The lack of understanding about the insurance also be the factor of the problem occur among the contractor. This research has done through interviews with the person that conducting or working with the Islamic Insurance company or conventional insurance company such Takaful Nasional Berhad and Takaful Malaysia Berhad. Beside, some questionnaires will be distributed among contractors. This research has been conducted by smart planning and proper implementation. It is because we need to handle human that more difficult than handling a machines. From the research it showed that Conventional Insurance is still dominant in the market of construction project. Thus, it is expect that in the future, employers or contractors will realize the benefit of choosing insurance product by considering many aspects including the financial of insurance company, performance of services, fairness in processing claim and others. Proper construction records also necessary to demonstrate cause, effect, entitlement, and quantification of damages incurred by the contractor.